Unstable Angina /Non ST Elevation Myocardial Infarction: Frequency of Conventional Risk Factors; TIMI Risk Score, and Their Impact On Angiographic Data - Mahmood, Ghassan M.; AL- Marayati, Amal N. (AL-Kindy College Medical Journal, 2014)
Background: Appreciation of the crucial role of risk factors in the development of coronary artery disease (CAD) is one of the most significant advances in the understanding of this important disease. Extensive epidemiological research has established cigarette smoking, diabetes, hyperlipidemia, and hypertension as independent risk factors for CADObjective: To determine the prevalence of the 4 conventional risk factors(cigarette smoking, diabetes, hyperlipidemia, and hypertension) among patients with CAD and to determine the correlation of Thrombolysis in Myocardial Infarction (TIMI) risk score with the extent of coronary artery disease (CAD) in patients with unstable angina /non ST elevation myocardial infarction (UA/NSTEMI).Methods: We conducted a descriptive study among 100 patients admitted with UA/NSTEMI to three major cardiac centers in Iraq: Iraqi Centre for Heart Disease ,Ibn- Al-Bitar Hospital for cardiac surgery and Al -Nasyria Cardiac Centre from January 2010 to January 2o11.Frequency of each conventional risk factors and number of conventional risk factors present among patients with CAD, compared between men and women and by age are estimated at study entry. The TIMI risk score was stratified on seven standard variables. The extent of CAD was evaluated on angiography and significant CAD was defined as ≥ 70% stenosis in any one of the three major epicardial vessels and ≥50% in LMS.Results : Among 100 patients with UA/NSTEMI , 82% of patients have one or more risk factors and only 18%of patients lacked any of 4 conventional risk factors.Smoking is the most common risk factor in male patients while diabetes mellitus and dyslipidemia are common among female patients, and all these results are statistically significant.There were 64 % patients with TIMI score < 4 (low and intermediate TIMI risk score) and 36% patients with TIMI score >4 (high TIMI risk score). Patients with TIMI score > 4 were more likely to have significant three vessel CAD and LMS versus those with TIMI risk score < 4 who have less severe disease (single and two vessel disease).Conclusion: Antecedent major CAD risk factor exposures were very common among those who developed CAD emphasizing the importance of considering all major riskfactors in determining CAD risk estimation . Patients with a high TIMI risk score were more likely to have severe multivessel CAD compared with those with low or intermediate TIMI risk score. Hence, patients with TIMI score >4 should be referred for early invasive coronary evaluation to derive clinical benefit.Key words: unstable angina , Thrombolysis in Myocardial Infarction score, risk factors